DINAMIKA ORGANISASI INTRA SEKOLAH DALAM MEMBENTUK KARAKTER SISWA YANG BERINTEGRITAS - syarqi, fia; Aminatus Sholihah, Siti; Risma Cahyani Pratama Putri, Nur; Mahendra Datta, Dicky; Khadavi, Jadid (As-Sulthan Journal of Education, 2024)
This research aims to analyze the dynamics of intra-school organizations in shaping the character of students with integrity at MAN 1 Probolinggo City. Intra-school organizations, such as the OSIS and Scouts, play an important role in developing student character, especially in instilling the values of integrity. The research method used is a qualitative approach with a case study design. Data was collected through interviews, observation, and documentation, involving intra-school organization administrators, members, and coaching teachers. The research results show that intra-school organizations at MAN 1 Probolinggo City play an active role in forming student character through various programs and activities. The dynamics of interaction between organizational members, leadership, and support from coaching teachers are important factors in the successful formation of character with integrity. Factors such as discipline, responsibility and cooperation taught in organizations also strengthen students' attitudes of integrity. However, there are several obstacles, such as lack of student participation in certain activities and limited resources, which affect the effectiveness of character formation. This research contributes to the development of strategies for strengthening intra-school organizations as an integral part of character education in schools.